Notification of crop varieties and registration of germplasm : Bread wheat variety UAS 347 - Desai, S. A. (The Indian Journal of Genetics and Plant Breeding, 2016)
Wheat is one of the major rabi crop in the peninsular zone of Indian wheat belt comprising Maharashtra and Karnataka states. Majority of the wheat crop is grown under rainfed condition in this zone where crop is exposed to early and terminal heat stress conditions as major abiotic factors. The brown and black rusts are also crucial biotic stresses that affect wheat yields. The wheat improvement efforts at Sanjaya Rajaram Wheat Laboratory of the University of Agricultural Sciences, Dharwad resulted in the development of bread wheat variety UAS 347 which was released by the Central Sub-Committee on Crop Standards, Notification and Release of Varieties for Agricultural Crops (CVRC) vide S.O. 2680(E) dated 1.10.2015 for timely sown, rainfed condition of Peninsular zone comprising states of Maharashtra and Karnataka